PHONOLOGICAL INTERFERENCE OF CIREBON LANGUAGE ON THE PRONUNCIATION OF HIJAIYAH LETTERS - Arwani, Wawan; Sa'dudin, Ihsan; Abdullah, Abdullah; Sanusi, Anwar (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2025)
This study investigates the phonological interference of the Cirebon language on the pronunciation of hijaiyah letters (the Arabic alphabet) among students at Nahdlatul Ulama Islamic High School for Boys (Madrasah ‘Aliyah Nahdlatul Ulama Putra), Buntet Cirebon. In multilingual Muslim communities such as Cirebon, Arabic is learned not only as a foreign language but also as a sacred language of worship and religious practice, making pronunciation accuracy both linguistically and spiritually significant. Based on phonetic observation and qualitative interviews, the research identifies systematic patterns of mispronunciation, particularly involving pharyngeal, uvular, and emphatic consonants, such as /ḥ/, /ʕ/, /q/, and /ṣ/. These patterns are documented through observations, audio recordings, and careful transcription using the International Phonetic Alphabet, allowing for detailed phonological analysis. The errors are categorized into substitution, simplification, and omission, revealing consistent tendencies rather than incidental mistakes. These deviations arise from the absence of corresponding phonemes in the Cirebon language, resulting in substitution, simplification, and assimilation processes that alter the original Arabic sounds. Such processes illustrate negative language transfer, in which learners plot unfamiliar Arabic phonemes onto the closest sounds available in their native phonological inventory. The findings demonstrate how articulatory limitations, limited phonetic awareness, and insufficient explicit instruction interact to reinforce these patterns. It also reveals that the Cirebonese phonological system exerts a strong influence on the learners’ production of Arabic phonemes, demonstrating how local linguistic structures mediate the acquisition of a non-native phonetic inventory. This influence is not merely technical but sociolinguistic in nature, as Arabic pronunciation practices in Cirebon are shaped by daily communication, religious discourse, and pesantren traditions that normalize localized articulations. This research highlights the Cirebon language’s hybrid phonological features, shaped by influences from both Javanese and Sundanese, which reflect distinctive articulation patterns. This hybrid linguistic character makes Cirebon a unique and previously underexplored site for examining cross-linguistic phonological interaction in Indonesia. The study extends empirical evidence on how regional phonology affects Arabic sound realization in an Islamic sociolinguistic context. Beyond its descriptive contribution, the research offers a foundation for future work in interlanguage phonology, sociophonetics, and Arabic pedagogy, particularly in contexts where religious language learning intersects with strong local linguistic identities.